Correlation of Vitamin B12 Deficiency with Blood Glucose Level in Pregnant Females of Tertiary Care Hospital, KP - Mohammad Noman Yousaf, Sajida Shaheen, Nighat Fatima, Mehwish Bibi, Abid Ullah Shah, Imran Qadir Khattak (Pakistan Journal of Medical & Health Sciences, 2022)
Background: A developing fetus can be adversely affected by gestational diabetes mellitus (GDM). This condition is prevalent among South Asian women. A contributing factor to GDM is insulin resistance (IR). Only a few B12 and folate markers have been studied in association with GDM and IR, as studies have shown vitamin B12 (B12) and folate status to be associated with GDM. Objective: The current study aimed to determine the association between Vitamin B12 and folate markers and insulin resistance in pregnant women with GDM and NGT. Methods: Pakistani women (29 GDM and 41 NGT) with a mean age of 29 y, BMI, and gestational age of 33 weeks were included in the research. The serum total vitamin B12, and other parameters like folate, methylmalonic acid, plasma homocysteine and 5-methyl tetrachloro folic acid (RCF). The T-tests and chi-squared test and spearman’s correlation test were used to determine whether there was any correlation between vitamin B12 and blood glucose levels in pregnant women with and without gestational diabetes. A simple multiple regression analysis was used to see whether B12 and folate status indicators predicted Insulin Resistance (IR). Results: There was no statistically significant difference between NGT and GDM, demonstrating that both groups have the same features. Although a significant difference was found between BMI (p=0.037), Serum Fasting Glucose (p=0.001), HOMA_IR (p=0.001), Serum HDL (p=0.001), Serum TC (p=0.040), and Systolic BP (p=0.001). Women in both groups took iron and folic acid supplements in roughly equal numbers. Still, the GDM group had an excess of women taking multivitamin supplements (P = 0.039) and women taking iron supplements (P=0.001). In Spearman’s analysis HOMA-IR correlated negatively with total serum B12 (P < 0.00). The regression model is statistically significant with (F=1.927, P=0.046) p-value is less than the alpha value. Coefficient of determination R2=0,309, which indicated that 30.9% variation came in the response variable due to the explanatory variable and the rest due to other unknown factors. Practical implication Conclusions: it is concluded that there is a significant correlation between vitamin B12, folate and blood glucose level in Pakistani pregnant women in the third trimester. Moreover, vitamin B12 and folic acid have an impact on fetal health, i.e., weight, length and circumference of the head and chest. Keywords: gestational diabetes Mellitus, HOMA-IR, normal glucose tolerance, Peshawar